(3GdhGajI aj TQM GdcGajIs - (3GdMSjfj GdCSJQGHGPj, GHf nTnQa TGrg, Qcf GdOjf, MSf Hf eMeO Hf TQaTGg, (B715 (3g`s ((3SdGR Hf CMeO Hf gdGd Hf eMeO GdHhQjs)
(3ChdgG (B:s
(3fGbU GdChd(B: (3hChdg HGdVe hGdaJM hGdcSQ bO jchf daXjG hbO jchf JbOjQjG HGdVeI hGdaJMI hGdcSQI bhdg ZjQ GdefUQas
(3BNQgG (B:s
(3EPG cGf ecShQG Ch hGhG EPG cGf eVeheG bjGSG Ydi Gdhba aj GdGSe hdCfg de jYde Cfg HOd Yf GdJfhjf hGdeMPha GdeQOhO hGddg CYde HGdUhGHs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 2 / 215s
(3eYLe GdeDdajf(B: 1 / 586s
(3cTa GdXfhf(B: 2 / 1370s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GdfMhs